Keefektifan Konseling Modifikasi Kognitif Perilaku untuk Menurunkan Stres Akademik Siswa - Yeni Karneli; Ardimen Ardimen; Netrawati Netrawati (Universitas Kanjuruhan Malang, 2019)
This research is motivated by the high level of academic stress students have. by showing the behavior of avoiding lessons, such as often leaving class when school hours, skipping lessons, not doing school work, ignoring school assignments. The purpose of this study was to determine the effectiveness of the cognitive behavioral modification counseling approach (KMKP) in reducing students' academic stress. The method used was quantitative with the Quasi experimental research design. The design form used was the pretest-posttest control group design. Data analysis using non-parametric statistics, namely Wilcoxon Signed Ranks Test. The results showed an effective behavioral modification counseling approach to reduce students' academic stress. This is evidenced because the behavioral cognitive modification counseling approach places great emphasis on changing the internal dialogue of the counselee.